Dolichoectasia and Small Vessel Disease in Young Patients With Transient Ischemic Attack and Stroke. Issue 9 (September 2017) - Thijs, Vincent; Grittner, Ulrike; Fazekas, Franz; McCabe, Dominick J.H.; Giese, Anne-Katrin; Kessler, Christof; Martus, Peter; Norrving, Bo; Ringelstein, Erich Bernd; Schmidt, Reinhold; Tanislav, Christian; Putaala, Jukka; et al.
Abstract : Background and Purpose—: We evaluated whether basilar dolichoectasia is associated with markers of cerebral small vessel disease in younger transient ischemic attack and ischemic stroke patients. Methods—: We used data from the SIFAP1 study (Stroke in Young Fabry Patients), a large prospective, hospital-based, screening study for Fabry disease in young (<55 years) transient ischemic attack/stroke patients in whom detailed clinical data and brain MRI were obtained, and stroke subtyping with TOAST classification (Trial of ORG 10172 in Acute Stroke Treatment) was performed. Results—: Dolichoectasia was found in 508 of 3850 (13.2%) of patients. Dolichoectasia was associated with older age (odds ratio per decade, 1.26; 95% confidence interval, 1.09–1.44), male sex (odds ratio, 1.96; 95% confidence interval, 1.59–2.42), and hypertension (odds ratio, 1.39; 95% confidence interval, 1.13–1.70). Dolichoectasia was more common in patients with small infarctions (33.9% versus 29.8% for acute lesions, P =0.065; 29.1% versus 16.5% for old lesions, P <0.001), infarct location in the brain stem (12.4% versus 6.9%, P <0.001), and in white matter (27.8% versus 21.1%, P =0.001). Microbleeds (16.3% versus 4.7%, P =0.001), higher grades of white matter hyperintensities ( P <0.001), and small vessel disease subtype (18.1% versus 12.4%, overall P for differences in TOAST ( P =0.018) were more often present in patients with dolichoectasia. Conclusions—: Dolichoectasia is associated with imaging markers of small vessel disease and brain stem localization of acute and old infarcts in younger patients with transient ischemic attack and ischemic stroke. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00414583. Abstract : Supplemental Digital Content is available in the text.